1901 Neb. Laws 372, art. II, ch. 36, § 4, pt. 8. - (:unkn) unknown (General Publisher, 1901)
No game shall be pursued, taken, wounded or killed in the night, nor with a steel or hard pointed bullet, nor with any weapon other than an ordinary shoulder gun or pistol
--
Keywords: HUNTING REGULATION